A Bibliometric Analysis of Atrophic Gastritis From 2011 to 2021 - Zhang, Tai; Zhang, Beihua; Tian, Wende; Ma, Xiangxue; Wang, Fengyun; Wang, Ping; Wei, Yuchen; Liu, Lin; Tang, Xudong (Frontiers in Medicine, 2022)
Background: Atrophic gastritis (AG), which is characterized by a decreased number or disappearance of the glandular structures and secretory dysfunction is linked to chronically inflamed stomach. It has been estimated that the annual incidence of gastric cancer (GC) is 0.1% for patients with AG. Early eradication of H. pylori can reduce the risk of GC development. Additionally, follow-up and management of AG is necessary to prevent GC. Exploring novel methods of the automatized analysis of data for apprehending knowledge in any medical field is encouraged, especially when a body of literature suggests the necessity of doing so. Accordingly, herein, we aim to systematically review the current foci and status of AG research using bibliometric analysis. Methods: Articles and reviews related to AG published from 2011 to 2021 in the Web of Science Core Collection were retrieved. Microsoft Office Excel 2019 and GraphPad Prism were used to show the annual number of publications and authors’ scientific productivity through time. CiteSpace and VOSviewer were used to generate network maps about the collaborations among countries, institutions and authors as well as reveal hotspots of AG research. The relationships among the author’s keywords, cited references and the top authors were summarized by a Sankey plot (three-fields plot). Results: A total of 1,432 publications were included in the present study. China remained the most productive country, with the highest number of publications (377, 26.32%). Vanderbilt University contributed the most publications of any single institution (56, 3.91%). JAMES R GOLDENRING was the most active and influential scholar, with the highest number of publications and greatest centrality. The most prolific journal in this field was WORLD JOURNAL OF GASTROENTEROLOGY (62, 4.32%). GASTROENTEROLOGY (997, 69.62%) was the most cocited journal. Exploring the origin of gastric metaplasia, especially SPEM was a major topic in AG research. Conclusions: This bibliometric study provides a comprehensive analysis of the scientific progress of AG over the past decade. Metaplasia is a hot topic and could be a promising area of research in the coming years.